2007
DOI: 10.1295/polymj.pj2006211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Property of Poly(arylene sulfone)s Containing 9,9-Diarylfluorene Moiety in the Main Chain

Abstract: ABSTRACT:Poly(arylene sulfone)s (PASs) were synthesized in quantitative yields by the oxidations of the corresponding fluorene-containing poly(arylene thioether)s, derived from 9,9-diarylfluorene-based dithiols and dihaloarenes, with 30% hydrogen peroxide in formic acid. PASs had good solubility in common organic solvents such as chloroform, N-methylpyrrolidone (NMP), and N,N-dimethylformamide (DMF). Highly transparent films were obtained by casting the chloroform solutions of PASs. PASs exhibited high glass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…These characteristic optical properties of the F-PEs come mainly from the cardo structure of the 9,9-diarylfluorene skeleton as well as the alkyl chains in the main chain. [1][2][3][4][5][6][7][8][9] In addition, the carbon filler (C 60 ) dispersing power of the F-PEs was confirmed and decreased with increase in length of the alkyl chain. Thus, the F-PEs can unambiguously be regarded as one of the potential polymer materials being used in a variety of fields including optical materials field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These characteristic optical properties of the F-PEs come mainly from the cardo structure of the 9,9-diarylfluorene skeleton as well as the alkyl chains in the main chain. [1][2][3][4][5][6][7][8][9] In addition, the carbon filler (C 60 ) dispersing power of the F-PEs was confirmed and decreased with increase in length of the alkyl chain. Thus, the F-PEs can unambiguously be regarded as one of the potential polymer materials being used in a variety of fields including optical materials field.…”
Section: Discussionmentioning
confidence: 99%
“…The PET film had clear birefringence, as showed in Figure 8, while the films of 3a and 3d hardly showed the birefringence, in accordance with the reports on other polymers containing 9,9-diarylfluorenes. [1][2][3][4][5][6][7][8][9] Degree of retardation at 590 nm in 3d (thickness: 250 mm) was less than 3.28 nm in undrawn state, 53 and the birefringence value was remarkably low (less than 1:3 Â 10 À5 ). In the drawn film of 3d (drawn ratio is 2.0), the birefringence value was À8:9 Â 10 À4 , and the stress optical coefficient was very low (À0:15 GPa À1 ).…”
Section: Birefringencementioning
confidence: 99%
See 2 more Smart Citations
“…It also has been reported that the incorporation of trifluoromethyl, sulfonyl, ketone, and/or ether moieties between benzene rings activates aromatic halide monomers and consequently accelerates a nucleophilic displacement reaction by generating aromatic diphenolate ions from the aromatic diols and results in a high molecular weight polymer during the polycondensation. [13][14][15] This article reports new PAEs produced from a nucleophilic substitution reaction of 4-fluoro-4'(((fluorobenzoyl)phenyl)-oxy)diphenyl sulfone) (FBPODS), an ordered sequence monomer, with cardo typed aromatic diols such as 9,9-bis (4-hydroxyphenyl)fluorene (BHPF), 1,3-bis(4-hydroxyphenyl)adamantane (BHPA), and 1,1-bis(4-hydroxyphenyl)cylclohexane (BHPC). Their thermal and mechanical properties, transparency, solubility, and water uptake will also be described.…”
Section: Introductionmentioning
confidence: 99%